Valuasi Penyelenggaraan Ujian Akhir Semester Mahasiswa Program Non Pendidikan dasar Di UPBJJ-UT Makassar - Kadariah, Kadariah (Universitas Negeri Makassar, 2018)
The study aims to describe the successful implementation of UAS Non Pendas program in UPBJJ-UT Makassar for the examination period 2017.1. The population in this study were students of UAS, PJTU, PJLU, PK, PR and Administrative Staff in UPBJJ-UT Makassar consisting of 191 respondents with 92 question items. The research data consist of evaluation result of successful implementation of UAS Non-Pendas program at UPBJJ-UT Makassar for the examination period 2017.1. Data analysis using descriptive statistics. The results showed that: 1). Responsible Examination Place (PJTU) and Responsible Exam Location (PJLU) performs the task well; 2). The traveling supervisor stated that the implementation of UAS Non Pendas program in UPBJJ-UT is effective and efficient; and 3). Perceptions of Administrative Staff on the implementation of UAS Non-Pendas program at UPBJJ-UT Makassar for the examination period 2017.1 is still less effective